Financial Innovation Strategies and Performance of Commercial Banks in Kenya - Mukira, Abubaker Ramathan; Kariuki, Paul; Muturi, Willy (Journal of Strategic Management, 2022)
Purpose: The purpose of the study was to establish the impact of financial innovation strategies on performance of commercial banks. Methodology: The study used census approach and targeted all the 41 commercial banks in Kenya. This is because the population is small. Senior Operations and the Senior Finance managers working in the headquarters of the commercial banks were targeted. This was therefore a total of 82 respondents. The research adopted cross-sectional survey. The study used both primary and secondary data. Primary data was collected using questionnaires while Secondary information was acquired from the commercial banks' audited financial statements. After quantitative data was obtained through questionnaires, it was prepared in readiness for analysis and keyed into statistical package for social sciences (SPSS) computer software (version 22) for analysis. Findings: Results from both primary and secondary data showed that financial innovation strategies had a positive and significant effect on performance of commercial banks. Recommendation: Policy makers have to be wary about increasing level of competition in the banking industry and put in place appropriate competitive strategies to mitigate the challenges that come with the competition. These competitive strategies will enhance their performance and eventual survival in the industry.